A pilot investigation of emotional regulation difficulties and mindfulness-based strategies in manic and remitted bipolar I disorder and major depressive disorder - Musket, Christie W. (Int J Bipolar Disord, 2021)
BACKGROUND: Both bipolar disorder and major depressive disorder are characterized by difficulties in emotion regulation. Little is known about which specific emotion regulatory patterns may be transdiagnostic versus disorder specific, and how such patterns change as a function of current mood states. METHODS: This preliminary investigation examined specific patterns of self-reported trait emotion regulation difficulties and mindfulness-based regulations strategies across four groups: remitted adults with bipolar I disorder (BD-remitted; n = 32), currently manic adults with bipolar I disorder (BD-manic; n = 19), remitted adults with major depressive disorder (MDD-remitted; n = 32), and healthy controls (CTL; n = 30). RESULTS: All three clinical groups reported significantly greater difficulties with emotion regulation and decreased overall mindfulness-based strategies. CONCLUSIONS: These results suggest that increased emotion regulation difficulties, decreased mindfulness, and increased emotion-driven impulsivity may be transdiagnostic across mood disorders and states, and that impulsivity may be particularly impaired during periods of mania.